1999
DOI: 10.1103/physrevc.61.024602
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism and characteristics ofT20ind+3He

Abstract: For backward elastic scattering of deuterons by 3 He, cross sections σ and tensor analyzing power T 20 are measured at E d = 140 − 270 MeV. The data are analyzed by the PWIA and by the general formula which includes virtual excitations of other channels, with the assumption of the proton transfer from 3 He to the deuteron. Using 3 He wave functions calculated by the Faddeev equation, the PWIA describes global features of the experimental data, while the virtual excitation effects are important for quantitative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, the evaluations performed to this time using this model lead only to a tiny deviation from the PWIA calculations mentioned above. Recently, the Hosei group 8) analyzed T 20 and κ 0 with the 3 He-n-p cluster model using an analogy between 3 He and the proton (T = 1/2, S = 1/2). They concluded that PWIA describes the global features of the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…However, the evaluations performed to this time using this model lead only to a tiny deviation from the PWIA calculations mentioned above. Recently, the Hosei group 8) analyzed T 20 and κ 0 with the 3 He-n-p cluster model using an analogy between 3 He and the proton (T = 1/2, S = 1/2). They concluded that PWIA describes the global features of the experimental data.…”
Section: Introductionmentioning
confidence: 99%